2010
DOI: 10.1016/j.cell.2009.12.043
|View full text |Cite
|
Sign up to set email alerts
|

BubR1- and Polo-Coated DNA Tethers Facilitate Poleward Segregation of Acentric Chromatids

Abstract: Summary The mechanisms that safeguard cells against chromosomal instability (CIN) are of great interest, as CIN contributes to tumorigenesis. To gain insight into these mechanisms, we studied the behavior of cells entering mitosis with damaged chromosomes. We used the endonuclease I-CreI to generate acentric chromosomes in Drosophila larvae. While I-CreI expression produces acentric chromosomes in the majority of neuronal stem cells, remarkably, it has no effect on adult survival. Our live studies reveal that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
151
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(171 citation statements)
references
References 47 publications
17
151
2
Order By: Relevance
“…The fact that BubR1 is not detectable at the centromeres of cid (Blower et al 2006) and cal1 mutants suggests that these two proteins might be essential for BubR1 localization at the centromere. BubR1 was also recently described to be bound to DNA tethers that have been observed to form between centric and acentric chromosome fragments of broken chromosome arms (Royou et al 2010) and at unprotected telomeres (Musaro et al 2008). Understanding BubR1's partners on DNA tethers, uncapped telomeres, centromeres, and kinetochores is an important challenge requiring further investigation.…”
Section: Resultsmentioning
confidence: 99%
“…The fact that BubR1 is not detectable at the centromeres of cid (Blower et al 2006) and cal1 mutants suggests that these two proteins might be essential for BubR1 localization at the centromere. BubR1 was also recently described to be bound to DNA tethers that have been observed to form between centric and acentric chromosome fragments of broken chromosome arms (Royou et al 2010) and at unprotected telomeres (Musaro et al 2008). Understanding BubR1's partners on DNA tethers, uncapped telomeres, centromeres, and kinetochores is an important challenge requiring further investigation.…”
Section: Resultsmentioning
confidence: 99%
“…Spindle forces and motor proteins drive chromosome movement during mitosis, but these do not engage chromosome fragments lacking a centromere. In Drosophila neuroblasts, acentric chromosomal fragments have been reported to partially segregate poleward [56] through kinetochore-independent microtubules and the chromokinesin Klp3a [57], which shares similarity to human KIF4A. Alternative models include the topological linkage or “tethering” of chromosome fragments to each other, as suggested by 5/8 Look-Seq examples in which the majority of fragments were unequally distributed to a single daughter [25], or perhaps onto other chromosomes, a mechanism analogous to the proposal that extrachromosomal DNAs (including DMs or viral episomes) could tether and segregate in trans with centromere-containing chromosomes [5860].…”
Section: Bringing It All Back Home: Reassembly Through Dna Repairmentioning
confidence: 99%
“…Because the two partner foci appear to be distributed more than several micometers apart, which is a great distance at the molecular scale, one interpretation of the nature of unrepairable IRIF is that the broken chromosome ends are disconnected and physically separated. A recent report showed that acentric chromosome fragments are tethered by protein linkers and can be delivered normally into two daughter cells upon cell division (Royou et al, 2010;Lammens et al, 2011). Therefore, the physical disconnection of the broken ends of DNA might be the true nature of unrepairable IRIF.…”
Section: Unrepairable Irif Account For An Accumulated Dose Of Radiatimentioning
confidence: 99%